Integration of an intelligent tutoring system in a course of computer network design - Verdú, Elena; Regueras, Luisa M; Gal, Eran; Castro, Juan P de; Verdú, María J; Kohen-Vacs, Dan (Educational Technology Research and Development, 2017)
INTUITEL is a research project aiming to offer a personalized learning environment. The INTUITEL approach includes an Intelligent Tutoring System that gives students recommendations and feedback about what the best learning path is for them according to their profile, learning progress, context and environmental influences. INTUITEL combines efficient pedagogical-based recommendations with freedom of choice and it introduces this tutoring support in different Learning Management Systems. During the INTUITEL project various software and pedagogical testing procedures were defined to provide the development teams with feedback, both summative and formative. The current paper describes the initial user test, which was conducted at the University of Valladolid for the course “Network Design”. The experiment was focused on real learners’ reactions to INTUITEL recommendations received by an INTUITEL-enabled LMS. Nineteen students participated in a two phase testing procedure in order to analyze the learners’ behavior with INTUITEL, as well as obtaining information about how learners perceive the influence and usefulness of the tutoring system in online learning courses. Results show that students with INTUITEL follow learning paths that are more suitable for them. Besides, the general satisfaction level of participants is high. Most learners appreciate INTUITEL, would follow its recommendations and consider the messages shown by INTUITEL as useful and caring.
Keywords: self-directed learning; personalized learning; intelligent tutoring systems; adaptive learning; semantic learning models; JCR; Scopus